‘Mdzlevari’ (triumphant) and ‘Mkvdarta Mze’ (the sun of dead) – Messengers of Two Countries, Two Worlds in Folk Speech - Arabuli, Amiran (Actual Problems of Kartvelology, 2025)
Name ‘Mdzlevari’(triumphant) unites three seasonal birds. These are: cuckoo, swallow and saxnaura (var, ”urnata”). They are associated with the messengers of two different countries, ot two diverse worlds (visible and invisible) in folk speech, as well as ‘Mkvdarta Mze’ (the sun of dead) is associated with astral images of tired god, ‘the dead sun’. ‘Mdzlevari’ (triumphant) and ‘Mkvdarta Mze’ (the sun of dead) become invisible periodically and according to people’s believes, they travel underneath the earth, they have two natures.